2021
DOI: 10.1007/s00467-021-05097-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of growth hormone in health and in kidney disease

Abstract: Growth hormone (GH) and its mediator insulin-like growth factor-1 (IGF-1) have manifold effects on the kidneys. GH and IGF receptors are abundantly expressed in the kidney, including the glomerular and tubular cells. GH can act either directly on the kidneys or via circulating or paracrine-synthesized IGF-1. The GH/IGF-1 system regulates glomerular hemodynamics, renal gluconeogenesis, tubular sodium and water, phosphate, and calcium handling, as well as renal synthesis of 1,25 (OH)2 vitamin D3 and the antiagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 240 publications
(287 reference statements)
1
34
0
5
Order By: Relevance
“…Elevated GH levels in humans (acromegaly) presented with signi cant structural hitherto functional changes in the renal system. Studies of the GH transgenic mice 31 , GH antagonist transgenic mice 32 , and pharmacological blockade of the GHR 33 revealed a more direct involvement of GH/GHR axis in the pathogenesis of DN [13][14][15][16]34 . An immediate action(s) of GH on the kidney was more evident upon the discovery of GHR and activation of canonical GH signaling cascade in podocytes 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated GH levels in humans (acromegaly) presented with signi cant structural hitherto functional changes in the renal system. Studies of the GH transgenic mice 31 , GH antagonist transgenic mice 32 , and pharmacological blockade of the GHR 33 revealed a more direct involvement of GH/GHR axis in the pathogenesis of DN [13][14][15][16]34 . An immediate action(s) of GH on the kidney was more evident upon the discovery of GHR and activation of canonical GH signaling cascade in podocytes 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that podocytes express IGF1 and its receptor IGF1R in control human glomeruli and that IGF1 protects podocytes from apoptosis in vitro [ 16 , 21 ] suggesting that an autocrine IGF1/IGF1R signaling may play a role in podocyte survival. Notably, dysregulation of the IGF1 system has been described in several kidney diseases, including diabetic nephropathy, polycystic kidneys and proteinuric kidney diseases [ 22 , 23 ]. According to our data, analysis of the glomerular transcriptomic dataset available on Nephroseq showed that IGF1 was downregulated in focal segmental glomerulosclerosis patients compared to healthy controls ( ; accessed on 24 Sempember 2021).…”
Section: Discussionmentioning
confidence: 99%
“… Physiological (main figure) and pathophysiological actions of GH (upper left insert) and IGF-1 on the kidneys. The original figure has been published by Hafner et al [ 107 ] and published here with permission. The figure is licensed under a Creative Commons Attribution 4.0 International License.…”
Section: Figurementioning
confidence: 99%